Integrated Geriatric Care Management in Hospitals: Systemic Clinical Problems in Older Adults, Assessment Approaches, and Management Strategies - Mohammad Aulia Molid Ogest Putra Calisanie; Zahratul Riadho; Lili Indrawati; Asyifa Robiatul Adawiyah (Dinasti Health and Pharmacy Science, 2026)
Indonesia entered population ageing in 2021, with residents aged 60 years and older exceeding 10% of the total population and projected to reach nearly 20% by 2045. Older adults present distinct clinical characteristics, namely multimorbidity, atypical disease presentation, and homeostenosis, that render single-organ approaches inadequate for hospital care. This review argues that geriatric syndromes are a major, modifiable driver of adverse outcomes in hospitalised older adults, and that their management should be embedded into existing hospital governance instruments rather than treated as a standalone clinical concern. A structured narrative review was conducted using PubMed (MEDLINE) with free-text and MeSH terms for geriatric syndromes, frailty, comprehensive geriatric assessment, polypharmacy, deprescribing, delirium, and falls; of 48 records identified, 30 studies met inclusion criteria after title/abstract and full-text screening. Findings indicate that geriatric syndromes, including immobility, instability, incontinence, delirium, malnutrition, sarcopenia, and polypharmacy-related iatrogenesis, are associated with poorer hospital outcomes; that multidisciplinary Comprehensive Geriatric Assessment increases the likelihood of patients remaining alive and at home after discharge; and that Beers- and STOPP/START-guided deprescribing, combined with multicomponent non-pharmacological bundles, reduces polypharmacy burden and helps prevent delirium and falls. These findings support integrating geriatric-specific indicators into hospital accreditation and National Quality Indicators, and establishing multidisciplinary geriatric teams as a governance priority.